Linking Remote Monitoring to Employee Performance: Mediating Role of Job Satisfaction - Khelalfa, Aboubaker Elseddik (Archives of Business Research, 2024)
The purpose of this research is to investigate the complex relationship between remote monitoring, employee task performance, and job satisfaction. Our main objective is to examine how remote monitoring impacts employee performance, with job satisfaction acting as a potential mediating factor. To do that we use the survey method to collect data from 300+ employees that use remote monitoring internationally. The data was analyzed using SSPA. The findings indicate a positive relationship between remote monitoring and task performance.